The Effect Of Compensation On Employee Performance At The Dairi Regency Tourism, Culture, Youth And Sports Office - Syahyunan; Abdi Sugiarto (International Journal of Management, Economic and Accounting, 2024)
This study aimed to analyze the effect of Compensation on Employee Performance at the Department of Tourism, Culture, Youth, and Sports of Dairi Regency. This research is a quantitative associative causal study using simple linear regression to examine the impact of the independent variable on the dependent variable. The study was conducted with a population of 96 employees, and the sampling technique used was saturated sampling, where all members of the population were included in the sample. Data were collected through a questionnaire distributed to all employees. The regression analysis showed that Compensation had a positive and significant effect on Employee Performance, with a regression coefficient of 1.673, meaning that every increase of one unit in Compensation would increase Employee Performance by 1.673 units. The coefficient of determination test resulted in an R Square value of 0.862, indicating that 86.2% of the variation in Employee Performance could be explained by the Compensation variable. The t-test produced a t-value of 24.251 > t-table 1.66123, with a significance value of 0.000 < 0.05, indicating that Compensation had a significant effect on Employee Performance. Overall, this study concluded that the implementation of Compensation can improve Employee Performance at the Department of Tourism, Culture, Youth, and Sports of Dairi Regency.